The Influence of Intellectual Capital on Profitability of Automotive Companies Listed on the Indonesia Stock Exchange - Addelia, Reza; Mediarta, Gde Ananta Yuga; Kasmawati, Kasmawati; Rahmawati, Rahmawati (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This research aims to examine the influence of intellectual capital, measured through the Value Added Intellectual Coefficient (VAIC™) method and its components (human capital efficiency, structural capital efficiency, and capital employed efficiency), on the profitability of automotive companies listed on the Indonesia Stock Exchange. Materials and methods: Data were collected from annual reports of 13 automotive and component companies listed on the Indonesia Stock Exchange from 2019 to 2023. Profitability was measured using Return on Assets (ROA) and Return on Equity (ROE). Multiple regression analysis was employed to analyze the relationship between VAIC™ components and profitability indicators. Results: The findings reveal a significant positive relationship between intellectual capital and company profitability. Human Capital Efficiency (HCE) demonstrated the strongest influence on profitability measures, followed by Capital Employed Efficiency (CEE). Structural Capital Efficiency (SCE) showed a positive but weaker relationship with profitability indicators. Companies with higher VAIC™ scores consistently displayed superior financial performance. Conclusions: Intellectual capital significantly contributes to the profitability of automotive companies in Indonesia. The findings suggest that automotive companies should prioritize investment in human capital development while also optimizing structural capital and physical capital to enhance their competitive advantage and financial performance in an increasingly knowledge-based industry.